Penal law protection of professional secrecy concerning the pension funds activities - Anna Płońska (Economic and Environmental Studies (E&ES), 2017)
This article is intended to introduce the Reader to the definition of professional secrecy as defined by Polish Organization and Functioning of Pension Funds Act (OFPF Act) and to highlight the essence of the most extensive legal protection of professional secrecy related to the activities of pension funds, which is the penal law protection.
Keywords: K42; G29; 330; professional secrecy; offence; pension funds